Motor conduction block and high titres of anti-GM1 ganglioside antibodies: pathological evidence of a motor neuropathy in a patient with lower motor neuron syndrome. Issue 9 (September 1993) - Adams, D; Kuntzer, T; Steck, A J; Lobrinus, A; Janzer, R C; Regli, F
Abstract : A patient with a progressive lower motor neuron syndrome and neurophysiological evidence of motor axon loss, multifocal proximal motor nerve conduction block, and high titres of anti-ganglioside GM1 antibodies. Neuropathological findings included a predominantly proximal motor radiculoneuropathy with multifocal IgG and IgM deposits on nerve fibres associated with a loss of spinal motor neurons. These findings support an autoimmune origin of this lower motor neuron syndrome with retrograde degeneration of spinal motor neurons and severe neurogenic muscular atrophy.